2010
DOI: 10.1136/bjsm.2010.071720
|View full text |Cite
|
Sign up to set email alerts
|

Sports injuries and illnesses in the 2009 FINA World Championships (Aquatics)

Abstract: Dette er siste tekst-versjon av artikkelen, og den kan inneholde ubetydelige forskjeller fra forlagets pdf-versjon. Forlagets pdf-versjon finner du på bjsm.bmj.com: http://dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
198
0
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(230 citation statements)
references
References 39 publications
23
198
0
9
Order By: Relevance
“…About half (50%) of these illnesses affected the respiratory system, and 20% affected the gastrointestinal system. Infection was the leading cause (49%), followed by environmental factors (28%; Mountjoy et al, 2010).…”
Section: Injury and Illness Prevalence In The Aquatic Disciplinesmentioning
confidence: 99%
See 1 more Smart Citation
“…About half (50%) of these illnesses affected the respiratory system, and 20% affected the gastrointestinal system. Infection was the leading cause (49%), followed by environmental factors (28%; Mountjoy et al, 2010).…”
Section: Injury and Illness Prevalence In The Aquatic Disciplinesmentioning
confidence: 99%
“…The other disciplines of FINA, including swimming, diving, marathon swimming, and synchronized swimming, were added to the surveillance program in the 2008 Olympic Games (Junge et al, 2009). FINA conducted its first injury surveillance at the 2009 FINA World Championships (Mountjoy et al, 2010). Illnesses were also compared between aquatics and other Olympic sports at the 2012 Olympic Games (Engebretsen et al, 2013).…”
Section: Injury and Illness Prevalence In The Aquatic Disciplinesmentioning
confidence: 99%
“…1 2 Although surveillance systems have successfully been implemented in major international sporting events [3][4][5][6][7][8][9][10] and a reduction in injury incidence following implementation of injury prevention strategies was demonstrated, 11 12 continuous health monitoring of athletes in out-of-competition phases is rare. 2 13-15 Several studies have shown that much higher injury rates are reported when athletes are continuously monitored than when they are evaluated retrospectively.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of overuse injuries in athletes with disability has been described in previous studies 6,8,9 but not in relation to specific sports. Mountjoy et al 22 also described a frequency of 35% overuse injuries when evaluating sports injuries in 5 aquatic sports. It is estimated that an able-bodied collegiate swimmer performs an average of more than 1 million strokes per arm per year 23 ; however, training loads among Paralympic swimmers are unknown.…”
Section: Discussionmentioning
confidence: 99%